Managing Request-Offer Negotiations under the GATS The Case of Environmental Services - Geloso Grosso, Massimo (OECD Trade Policy Papers, 2005)
This study forms part of on-going OECD work on trade in services, in co-operation with UNCTAD, aimed at assisting WTO Members in managing request-offer negotiations under the GATS. The key objective is to help officials of WTO Members in both gaining a greater insight into the particular issues of importance in the environmental services sector and how they might be approached in the negotiations. The current set of GATS negotiations offers WTO Members an opportunity to achieve greater levels of liberalisation of environmental services, which may lead to significant economic and environmental benefits for all countries. Nevertheless, liberalisation, particularly of environmental infrastructure services, must be appropriately designed and supported by a strong regulatory framework. Making commitments in these services thus raises questions in relation to their nature, although the flexibility provided for in the GATS can be used to schedule them to take account of their characteristics. Risks of market failure to achieve social objectives appear to be less significant for environmental non-infrastructure and support services